Public-private partnership for the delivery of veterinary services: Workshop report on the review and validation of PPP models for scaling out - Berhanu, Dagim; Desta, Hiwot; Gizaw, Solomon; Knight-Jones, Theodore J.D. (International Livestock Research Institute, 2025)
This workshop, held on 27 March 2025, at the International Livestock Research Institute (ILRI) Addis Ababa campus, was part of the Restoration of Livestock Services in Conflict and Drought-Affected areas of Ethiopia (RESTORE) project’s efforts to strengthen veterinary service delivery in conflict and drought-affected areas of Ethiopia. Bringing together government representatives from six regions, ILRI and the Ethiopian Veterinary Association (EVA) RESTORE teams, the RESTORE Technical Assistance Team (TAT), and NGOs, the event focused on reviewing public-private partnership (PPP) models tested under the Health of Ethiopian Animals for Rural Development (HEARD) project. Participants analysed lessons learned, validated successful models, and collaborated on a joint plan for scaling them out across the RESTORE and HEARD regions to enhance livestock health, productivity and resilience. The workshop focused on reviewing and validating public-private partnership (PPP) models previously tested under the HEARD project. Model I (Private vaccination service), Model II (Sanitary mandate), and Model VIII (Leasing public AHPs to unemployed graduates) were identified as the most suitable for scale-up. Key challenges highlighted included government subsidies and free NGO services undermining private sector involvement, limited cold chain capacity, vaccine supply shortages, unregulated drug markets, and gaps in legal and policy frameworks. The workshop emphasized the importance of gender integration, particularly including female-headed households, and encouraged treating pastoralist mobility as a resilience strategy rather than a barrier. The way forward includes scaling up successful PPP models with strong government ownership, tailoring models to regional needs, establishing supportive policies, and strengthening PPP taskforces, community animal health workers (CAHW) capacities, and infrastructure for long-term sustainability.